Bridging the Gap: E-commerce and the Rise of Rural Economies in Free Trade Zones - Lyu, Wenbo; Cao, Zhiyao; Zheng, Minqi; Zhang, Jie; Feng, Jinsun (Theoretical Key Issues and Practical Development Trends of China’s Digital Economy, 2024)
The integration of the digital economy and rural development is pivotal for the comprehensive advancement of the economy. This study examines the impact of the digital economy on rural revitalization within the context of Hainan's Free Trade Port, as outlined on July 1, 2021. Utilizing panel data analysis from all 16 Hainan districts, two hypotheses were proposed: the proliferation of the internet accelerates the digital economy and fosters rural rejuvenation, and enhanced talent quality elevates rural GDP. Empirical evidence supports these hypotheses, highlighting the digital economy's role in rural revitalization. Theoretical and practical implications suggest leveraging digital platforms to enhance agricultural marketing and advocating for e-commerce literacy programs to empower rural communities. The study concludes that strategic investments in digital infrastructure and talent development are essential for sustainable rural development, offering valuable insights for policymakers aiming to bridge the urban-rural divide in the digital era.